The Role Of Local Governments In Tackling The Covid-19 Pandemic - Shelva Shendy (Socio Legal and Islamic Law, 2022)
The existence of an emergency caused by Covid-19 has made the Government declare Covid-19 a national disaster. However, because the Central Government was not fast in issuing Government Regulation No. 21 of 2020 concerning Large-Scale Social Restrictions (PSBB) in the context of Accelerating Covid-19 Handling on March 31, 2020, resulting in Regional Governments taking steps earlier than the Central Government in handling Covid-19. This research uses normative legal research methods using literature research, namely conducting research on library materials and secondary data in the form of journals, articles, and laws related to the Role of Local Governments in Overcoming the Covid-19 Pandemic. The results showed that based on Law No. 23 of 2014 concerning Regional Government, to overcome the Covid-19 pandemic, the Regional Government has the authority to determine a policy. Such as the policy of the Regional Government in implementing the lockdown mechanism. In addition, the Regional Government has also taken several steps to overcome Covid-19. Such as suppressing the acceleration of the spread of Covid-19 by means of 3M discipline (washing hands, maintaining distance, and using masks), accelerating vaccination in the regions, creating many labor-intensive programs in their respective regions, and also distributing social assistance to people affected by Covid-19.